Factors associated with an increased risk of opioid misuse among patients with non-cancerpain in Malaysian pain clinic settings - Sani, Asween R.; Hj. Mohd. Zin, Che Suraya (Taylor & Francis, 2024)
This study examined the factors associated with a high risk of opioid misuse among patients receiving opioid treatment for their non-cancer pain in Malaysian pain clinics. The Screener and Opioid Assessment for Patients with Pain-Revised (SOAPP-R), a validated instrument for predicting the risk of aberrant drug-related behaviors, were used as a proxy to indicate risk of opioid misuse. Data analysis was stratified into high-risk and low-risk patient groups. Patient factors assessed included pain intensity, pain interference with daily activities, and health-related quality of life. Prescription opioid exposure was examined via patient medical and prescription records review. Among the 61 patients recruited, 62.3% scored ≥18 on the SOAPP-R, which indicates a high risk for opioid misuse. Factors associated with a high risk of opioid misuse were found to be high level of pain interference with daily activities, poorer mental health, and younger age. High-risk patients were found to be prescribed a lower mean daily opioid dose of <20 mg/day compared to low-risk patients (20–49 mg/day). This highlights the need for further research to distinguish aberrant drug related behaviors due to inadequate pain management from that of actual prescription opioid misuse among non-cancer pain patients attending pain clinics.